Analisis Prosedur Pemberian Kredit dan Pengikatan Jaminan pada KSP BALO’TA Cabang Tarakan - Oktofian Bannepadang; Yoel Pasae; Yunus Sirante (Penerbit Goodwood, 2025)
Purpose: The study aims to evaluate compliance with SOPs, prudence principles, and legal regulations, while also identifying operational, legal, and credit risks, along with the cooperative’s mitigation strategies. Methodology/approach: The method used is qualitative descriptive through observation, interviews, and document analysis. Results/findings: The findings indicate that credit procedures largely comply with SOPs and prudential principles via 5C analysis. However, improvements are needed in document verification, credit scoring, digital collateral archiving, and limiting informal collateral binding. Key risks include non-performing loans, invalid borrower data, and weak legal standing of informal collateral, mitigated through persuasion, field checks, and cooperation with notaries/PPAT. Conclusions: While the current procedures are systematic and legally aligned, strengthening technological support, formalizing collateral binding, and enhancing risk management are crucial for sustaining cooperative performance. Limitations: This research focuses on analyzing credit distribution procedures and collateral binding at KSP BALO’ Toraja Tarakan Branch, limited to their compliance with SOPs, prudential principles, and legal provisions. Contribution: This research contributes to cooperative financial management and business law literature, providing practical recommendations for improving credit procedures, collateral binding, and risk mitigation in savings and loan cooperatives.